La comunicación interna y su incidencia en el desarrollo organizacional del Gobierno Autónomo Descentralizado Municipal del cantón Tosagua, período 2019-2020 - Cedeño Párraga, Gissela Annabell (2022)
The objective of this research was to analyze the incidence of internal communication in the Municipal Autonomous Decentralized Government in Tosagua Canton, for the improvement of organizational development. The methodology used in the investigation was documentary and field, through applied instruments such as; interview, survey, and observation where the aspects that affect the communicative environment of the institution were diagnosed and identified. Once the information has been collected, the most relevant results show little training and professional qualification, lack of communication channels, lack of communicative effectiveness between workers and their immediate superior, distortion of the context of the message and poor interpersonal relationships, in addition, the poor organizational climate and motivation in public servants. Finally, it is concluded that there is a need for an action plan for the directors of the entity for their respective consideration, focused on administrative management tools that contribute to organizational improvement.